Towards optimal energy efficiency: analysing generalized and tailored retrofitting decisions - Wilamy Castro; Joana Barrelas; Maria Paula Mendes; Christoph Reinhart; Ana Silva (Discover Applied Sciences)
Abstract A building’s energy performance, in terms of thermal comfort, energy demand, cost and CO2 emissions, is considerably affected by its envelope. Enhancing energy efficiency through maintenance and retrofitting is essential to reduce consumption and emissions, thereby mitigating climate change. However, selecting the most cost-effective retrofitting solution remains challenging for decision-makers. Analysing real data across multiple scenarios provides valuable insights, supporting informed decision-making. This study discusses the impact of thermal retrofitting decisions on the energy efficiency of an existing single-family home, by analysing multiple scenarios concerning the implementation of measures on external walls, roof and windows. Both generalized and tailored approaches, particularly for external walls, are evaluated. Options include different insulation materials for the roof and façades—with the latter employing an external thermal insulation composite system (ETICS)—and various framing materials with double-glazing for window replacement. Various scenarios are discussed based on thermal simulations, implementation costs, and cost-benefit analysis. Additionally, multi-criteria (MCA) and sensitivity (SA) analyses are conducted to determine the optimal retrofitting solution. The most effective combined strategy applies ETICS with rock wool on the external walls, extruded polystyrene panels on the roof, and aluminium-framed windows with a thermal break, balancing energy efficiency, costs, durability, and sustainability. Although not part of the optimal solution, tailored retrofitting of façade F2 presents a viable alternative under cost constraints.